In vitro assay of biological activity of a national preparation of macrophage activating factor (GcMAF-RF) - E. V. Levites; S. S. Kirikovich; E. V. Dolgova; A. S. Proskurina; G. S. Ritter; А. A. Ostanin; E. R. Chernykh; S. S. Bogachev (Вавиловский журнал генетики и селекции)
The article reports an original method for producing vitamin D3-binding protein (DBP) and its conversion into macrophage-activating factor GcMAF-RF. According to an original protocol, DBPs were obtained from human blood plasma using affinity chromatography, purified and modified to GcMAF-RF using cytoimmobilized glycosidases (beta-galactosidase and neuraminidase). The presence of the polypeptide obtained in the Gc group of blood plasma globulins was confirmed by Western blot using specific antibodies. The molecular properties of this polypeptide put it in correspondence with the GcMAF protein described in the literature, which is undergoing clinical trials in the USA, Britain, Israel and Japan (at Saisei Mirai; Reno Integrative Medical Center; Immuno Biotech Ltd; Efranat; and Catalytic Longevity). The biological activity of the GcMAF-RF preparation was detected by the induction of phagocytic activity of macrophages and their ability to produce nitrogen monoxide (NO) in vitro.The phagocytic activity of macrophages was evaluated by their ability to uptake magnetic beads. The degree of activation of macrophages was calculated by the ratio of trapped beads to the total number of macrophages. The level of NO production was estimated by the accumulation of nitrogen monoxide in the culture supernatants of peritoneal macrophages by the colorimetric method using the Griess reagent. It was shown that GcMAF-RF multiplies the phagocytic activity of macrophages and significantly increases their production of nitrogen monoxide. The macrophage activator GcMAF-RF, according to its characteristics, corresponds to similar preparations which are made available to the market by foreign companies, and can be considered as a new biologically active preparation with a wide spectrum of action. Of greatest interest is its ability - through the activation of macrophages - to enhance the adaptive immunity. In this regard, two areas of therapeutic use of the GcMAF-RF are proposed. The preparation will be in demand in the field of cancer treatment, and, in addition, it can be used in the treatment of a number of neurodegenerative pathologies.